A relevância da racionalidade comunicativa para a gestão educacional - Scarlatto, Elaine Cristina [UNESP]; Gentilini, Joao Augusto [UNESP] (My University, 2012)
This study presents implications of the assumptions of a model of educational management based on the perspective of technical and instrumental rationality regarding fundamental studies of the Frankfurt School and Gentilini (2001). We analyzed the presence of such theoretical assumptions in the Complementary Education Program “Prof. Henrique Scabello” implemented in the city of Araraquara, SP. The results indicate that this model of educational management brings negative implications for the school investigated, and above all that adherence to the management model based on communicative rationality can favor the realization of a truly democratic school management.

Este estudo apresenta implicações dos pressupostos de um modelo de gestão educacional fundamentado na perspectiva da racionalidade técnica e instrumental, tendo como referências fundamentais os estudos da Escola de Frankfurt e Gentilini (2001). Analisou-se a presença de tais pressupostos teóricos no Programa de Educação Complementar (PEC) “Prof. Henrique Scabello”, localizado na cidade de Araraquara-SP. Verificou-se que o referido modelo de gestão educacional traz implicações negativas à organização escolar investigada. E, sobretudo que a adesão ao modelo de gestão baseado na racionalidade comunicativa pode beneficiar a realização de uma gestão de ensino efetivamente democrática.
The relevance of communicative rationality to educational management
Keywords: Rationality; Communication; Educational Management; Racionalidade; Comunicação; Gestão Educacional